The association between tranexamic acid and convulsive seizures after cardiac surgery: a multivariate analysis in 11 529 patients1. (19th December 2013) - Sharma, V.; Katznelson, R.; Jerath, A.; Garrido‐Olivares, L.; Carroll, J.; Rao, V.; Wasowicz, M.; Djaiani, G.
Summary Because of a lack of contemporary data regarding seizures after cardiac surgery, we undertook a retrospective analysis of prospectively collected data from 11 529 patients in whom cardiopulmonary bypass was used from January 2004 to December 2010. A convulsive seizure was defined as a transient episode of disturbed brain function characterised by abnormal involuntary motor movements. Multivariate regression analysis was performed to identify independent predictors of postoperative seizures. A total of 100 (0.9%) patients developed postoperative convulsive seizures. Generalised and focal seizures were identified in 68 and 32 patients, respectively. The median (IQR [range]) time after surgery when the seizure occurred was 7 (6–12 [1–216]) h and 8 (6–11 [4–18]) h, respectively. Epileptiform findings on electroencephalography were seen in 19 patients. Independent predictors of postoperative seizures included age, female sex, redo cardiac surgery, calcification of ascending aorta, congestive heart failure, deep hypothermic circulatory arrest, duration of aortic cross‐clamp and tranexamic acid. When tested in a multivariate regression analysis, tranexamic acid was a strong independent predictor of seizures (OR 14.3, 95% CI 5.5–36.7; p < 0.001). Patients with convulsive seizures had 2.5 times higher in‐hospital mortality rates and twice the length of hospital stay compared with patients without convulsive seizures. Mean (IQR [range]) length of stay in the intensive care unit was 115 (49–228 [32–481]) h in patients with convulsive seizures compared with 26 (22–69 [14–1080]) h in patients without seizures (p < 0.001). Convulsive seizures are a serious postoperative complication after cardiac surgery. As tranexamic acid is the only modifiable factor, its administration, particularly in doses exceeding 80 mg.kg−1, should be weighed against the risk of postoperative seizures.